Study on transmission over Nakagami-m fading channel for multiple access scheme without orthogonal signal - Chi-Bao Le; Dinh-Thuan Do (Universitas Ahmad Dahlan, 2020)
In this paper, a downlink performance in non-orthogonal multiple access (NOMA) system is considered. With regard to different priority for two NOMA users, we exploit the closed-form expressions of outage probability over wireless fading channel following Nakagami-m fading. The fixed power allocation factor scheme is examined to reduce the complexity in computation regarding performance analysis. In our analysis, perfect successive interference cancellation (SIC) is applied in order to achieve perfect signal decoding operation. Simulation results show that the considered NOMA downlink scheme is affected by transmit SNR, power allocation factors, fading parameters.